Análisis del sistema de gestión administrativa Fénix de la Cooperativa Santa Rita de la ciudad de Babahoyo - Herrera Mendieta, Layda Zenaida (2021)
Administrative management systems seek to help the management of a company with the automation of operations, that is why in the development of this case study an analysis of the FÉNIX administrative management system was carried out for the Santa Rita de la Ciudad cooperative of Babahoyo. The qualitative approach is used as a methodology for the collection of information, the interview will be used as a research technique and a questionnaire will be implemented as a research instrument, in order to obtain the data to carry out the pertinent analysis, subsequently obtaining the necessary information and Finally, the conclusions and recommendations that have been reached were presented.